2013
DOI: 10.5402/2013/876724
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Age at First Delivery and Risk of Cardiovascular Disease Later in Life

Abstract: Background. To elucidate the association between maternal age at first delivery and cardiovascular health in women. Material and Method. A nationally representative survey, comprising 3,937 Finnish women aged 30-99 years with information on most of the potential cardiovascular disease (CVD) risk factors. Weighting survey analyses and logistic regression were performed. Results. Women who had their first delivery at age 25 or less had about five times higher odds ratio for myocardial infarction (fully adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Our study showed that parity is positively associated with BMI, while age at first pregnancy had an inverse association with PBF and subcutaneous fat of trunk and a positive association with the skeletal fat of arms and legs. Childbirth at a younger age and increased parity have been independently associated with central obesity for women later in life due to increased stress or changes in the lifestyle factors which is in partial agreement with our study [ 72 , 76 ]. For example, studies on Korean and US postmenopausal women showed similar results [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that parity is positively associated with BMI, while age at first pregnancy had an inverse association with PBF and subcutaneous fat of trunk and a positive association with the skeletal fat of arms and legs. Childbirth at a younger age and increased parity have been independently associated with central obesity for women later in life due to increased stress or changes in the lifestyle factors which is in partial agreement with our study [ 72 , 76 ]. For example, studies on Korean and US postmenopausal women showed similar results [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a young age at first birth (<20 years) has previously been linked to increased risk of cardiovascular disease and mortality in American women 1–4. Similarly, Finnish women who had their first child before age 25 years had increased risk of myocardial infarction and arrhythmia 5. In contrast, the biodevelopmental view suggests that childbearing should occur earlier in life, shortly after the reproductive system has matured,1 although this theory has received little support from empirical population studies.…”
Section: Introductionmentioning
confidence: 99%
“… 1–4 Similarly, Finnish women who had their first child before age 25 years had increased risk of myocardial infarction and arrhythmia. 5 In contrast, the biodevelopmental view suggests that childbearing should occur earlier in life, shortly after the reproductive system has matured, 1 although this theory has received little support from empirical population studies. Most previous research has focused on the health of women; however, more recently, work on age at first birth and later health has been extended to look at the long-term health of young fathers.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals, especially women, who grow up in disadvantaged families are more likely to enter parenthood at earlier ages (Pears et al, 2005) and have more children over the life course with shorter birth spacing (Setty-Venugopal & Upadhyay, 2002). Early transition to parenthood can lead to physiological tolls for women, such as hypertension and excessive weight gain, which may persist for decades after childbirth (Adamo et al, 2012), thus increasing risk for cardiovascular diseases in later life (Kharazmi et al, 2013). …”
Section: Introductionmentioning
confidence: 99%